SITUATION OF PUBLISHING PAPERBACKS IN LITHUANIA - KAŠĖTAITĖ, RASA (Knygotyra, 2010)
Paperbacks take an important place in Western publishing culture and the life of book readers. However, the same cannot be said about Lithuania’s publishing situation. There is a lack of information and research concerning this field. Taking notice of the experience of Great Britain and USA in publishing paperbacks, the main body of this paper examines the situation and possibilies of publishing paperbacks in Lithuania. A historical overview showed that publishing smaller size and softcover books in Lithuania was caused by a difficult political and economical situation. Hardcover long-lasting books were always preferred by Lithuanian readers. The increase of paperbacks in 2008–2009 was caused by the economic crisis. A need for cheaper books was felt, and numerous publishing houses offered a bigger range of pocketbooks; they were examined by themes and statistical analysis. Also, the main positioning and marketing startegies were investigated. To find out book readers’ opinion, workers of publishing houses and book shops as well as book users were interviewed. Lithuanian book buyers were found to accept detectives, love stories and popular literature produced in paperbacks. Other types of fiction literature encounter some difficulties: the distribution system of paperbacks is not suitable for this type of books – they are harder to notice and lose the advantage of a lower price at book auctions. Therefore, Lithuanian book buyers still prefer hardcover books, although accepting the fact that such factors as a lower price and a comfortable format when reading outside are important.